2012
DOI: 10.1590/s0102-67202012000400006
|View full text |Cite
|
Sign up to set email alerts
|

Instabilidade de microssatélite - MSI nos marcadores (BAT26, BAT25, D2s123, D5S346, D17S250) no câncer de reto

Abstract: HEADINGS -Microsatellite instability. Tumor markers, biological. Trasanal endoscopic microsurgery.ABSTRAT -Background -Colorectal cancer has an important genetic component.Microsatellites are considered phenotypic markers of prognosis, therapeutic response and identify patients with mutations in DNA repair genes. Aim -To evaluate the molecular profile of tumors underwent to transanal endoscopic microsurgery -TEM in surgical treatment of rectal cancer. Method -Thirty eight surgical specimens were evaluated acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 20 publications
0
13
0
4
Order By: Relevance
“…MSI can be considered a promising prognostic marker for CRC patients and MSI status can be assessed through a panel of five markers ( BAT25 , BAT26 , D2S123 , D5S346 , and D17S2720 ) and the use of polymerase chain reaction (PCR). MSI-high is characterized by instability at two loci or more, and MSI-Low by instability at one locus[39]. Currently, the main clinical use of MSI testing is to detect patients with Lynch syndrome.…”
Section: Tissue- Based Biomarkersmentioning
confidence: 99%
“…MSI can be considered a promising prognostic marker for CRC patients and MSI status can be assessed through a panel of five markers ( BAT25 , BAT26 , D2S123 , D5S346 , and D17S2720 ) and the use of polymerase chain reaction (PCR). MSI-high is characterized by instability at two loci or more, and MSI-Low by instability at one locus[39]. Currently, the main clinical use of MSI testing is to detect patients with Lynch syndrome.…”
Section: Tissue- Based Biomarkersmentioning
confidence: 99%
“…Liengswangwong et al reported MSI-low and MSS in liver fluke infection-associated intrahepatic CCA (34). In addition, the prognostic and predictive impacts of MSI status in patients with colon cancer have been reported (35,36). Previously, it was demonstrated the generation of a mutator phenotype in yeast was caused by imbalanced BER (37).…”
Section: Discussionmentioning
confidence: 99%
“…The identification process is based on analyzing the difference in the length of microsatellite repeats in tumor tissue compared to the healthy non-neoplastic tissue surrounding the tumor. Generally, panels of 10 markers [ 67 ] and commercially available kits [ 68 , 69 ] are in use, as well as a panel proposed by Bethesda [ 7 , 70 , 71 ].…”
Section: Diagnostics Of Lsmentioning
confidence: 99%